Bioactivity screening of selected Moroccan medicinal and aromatic plants, and the chemical basis of the phytotoxicity of caper, Capparis spinosa L. - Kisiriko, Musa; Bitchagno, Gabin T. M.; Harflett, Claudia; Noleto-Dias, Clarice; Naboulsi, Imane; Anastasiadi, Maria; Terry, Leon A.; Sobeh, Mansour; Beale, Michael H.; Ward, Jane L. (Elsevier, 2025)
Plant natural products are potential sources of biostimulants that can help plants overcome the effects of stress. The adverse effects of soil salinity on wheat growth necessitate the exploration of alternative sustainable solutions, such as biostimulants from medicinal and aromatic plants, to enhance crop resilience and productivity. This study aimed to screen nine Moroccan medicinal and aromatic plant extracts for their effect on wheat growth under saline and non-saline conditions using a seed soaking treatment, in a completely randomised experiment. Except for Marrubium vulgare leaf and Origanum compactum extracts, which averagely improved root length by 25 % and 14 %, respectively, none of the other extracts had significant positive effects on wheat seedling growth. Capparis spinosa (caper) extracts inhibited wheat emergence and growth, with leaf extracts being more phytotoxic than the stem extracts. The leaf extracts of C. spinosa caused an average reduction of the leaf length, root length, shoot dry weight and root dry weight of the wheat seedlings by 31 %, 21 %, 92 % and 94 %, respectively, compared with the control. Further fractionation of the leaf crude extract and follow-up screening revealed that the phytotoxicity likely resulted from a synergy between compounds in different fractions. Chemical analysis of the most active fraction by UHPLC-MS and NMR revealed loliolide as the major compound, alongside oxylipins and indole alkaloid derivatives. Additionally, a previously undescribed compound, 8-(1H-indol-3-yl-methyl)rutin, was also identified. These compounds potentially contribute to the phytotoxicity. The results of this experiment show that although two extracts enhanced root length, overall biostimulant effects were minimal, with C. spinosa extracts being significantly toxic, indicating the need to prevent their application on wheat.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3004 Crop and Pasture Production; Complementary and Integrative Health; Dietary Supplements; 2 Zero Hunger; Biotechnology; 3006 Food sciences; 4004 Chemical engineering; Capparis spinosa; Phytotoxic; Inhibitory; Oxylipins; Alkaloids; Loliolide; 8-(1H-indol-3-yl-methyl)rutin